A perspective on problems and prospects for academic publishing in Geography. Issue 1 (19th February 2016) - Meadows, Michael; Dietz, Ton; Vandermotten, Christian
Abstract : This commentary highlights problems of inequity in academic publishing in geography that arise from the increasing use of metrics as a measure of research quality. In so doing, we examine patterns in the ranking of geographical journals in the major global databases (e.g. Web of Science, Scopus) and compare these with a more inclusive database developed by the International Geographical Union. The shortcomings of ranking systems are examined and are shown to include, inter alia, linguistic bias, the lack of representation of books and chapters in books, the geographical unevenness of accredited journals, problems of multi‐authorship, the mismatch between ranking and social usefulness and alternative or critical thinking, as well as differences between physical and human geography. The hegemony of the global commercial publishing houses emerges as problematic for geography in particular. It is argued that the global community of geographers should continue to challenge the use of bibliometrics as a means of assessing research quality. Abstract : This commentary considers a range of current issues concerning the publishing of research articles in the discipline of geography. The hegemony of the global commercial publishing houses emerges as problematic for geography in particular. It is argued that the global community of geographers should continue to challenge the use of bibliometrics as a means of assessing research quality. e00016 Journal metrics and linguistic hegemony